2004
DOI: 10.1080/07315724.2004.10719401
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Some Antipsychotics on Erythrocyte Magnesium and Plasma Magnesium, Calcium, Copper and Zinc in Patients with Paranoid Schizophrenia

Abstract: We consider plasma Cu(2+)/erythrocyte Mg(2+) and plasma Cu(2+)/Zn(2+) ratio two important biological markers of the acute paranoid schizophrenia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
23
1
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(29 citation statements)
references
References 9 publications
4
23
1
1
Order By: Relevance
“…15 In a study conducted on 56 patients suffering from schizophrenia, erythrocyte and plasma Zn levels were found to be reduced. 16 In another study, no significant difference was seen in Zn levels between patients of schizophrenia and control. 17 It was concluded that Zn deficiency during gestation might be a factor in causing brain anomalies and schizophrenia, but after birth these changes may not be associated with the patient's nutritional status.…”
Section: Introductionmentioning
confidence: 96%
“…15 In a study conducted on 56 patients suffering from schizophrenia, erythrocyte and plasma Zn levels were found to be reduced. 16 In another study, no significant difference was seen in Zn levels between patients of schizophrenia and control. 17 It was concluded that Zn deficiency during gestation might be a factor in causing brain anomalies and schizophrenia, but after birth these changes may not be associated with the patient's nutritional status.…”
Section: Introductionmentioning
confidence: 96%
“…Some authors have reported a higher or decreased Mg concentration in the CSF of schizophrenic patients, a decreased plasma Mg or unchanged plasma Mg concentration before neuroleptic therapy and a decreased level after neuroleptic therapy in schizophrenic patients. A lower Mg level in the erythrocytes of schizophrenic patients has been obtained. Erythrocyte Mg concentration is higher after haloperidol and risperidone treatment than in the erythrocytes of schizophrenic patients pre‐drug treatment and increased Mg erythrocytes concentration is important for antipsychotic action of these neuroleptics .…”
Section: Discussionmentioning
confidence: 87%
“…This is because of inhibition of NMDA receptors on GABA neuron (main inhibitory pathway in the CNS) and there are no inhibitions of the major excitatory pathway that innervates the cerebrocortical and limbic brain region . To date, only a few studies have been performed on Mg and Ca concentration in patients with schizophrenia and consistent results have not been obtained . The majority of investigations determined the concentration of Mg and Ca in serum or plasma, which does not reflect the true state of the supply of the organism with Mg, as only 1% of the Mg is in blood plasma.…”
mentioning
confidence: 99%
“…Huang et al (2004) injected magnesium sulfate to pregnant women with high blood pressure and calculated serum calcium 4 hrs later. They observed that serum calcium is decreased significantly 12 . observed that treatment of preeclamptic women leads to 25% decrease in total calcium and 12% decrease in ionic calcium 13 .…”
mentioning
confidence: 99%